France Borko (1904–1956) - Borko, Gabrijel Elko (University of Maribor Press, 2024)
The 8th book of Personalities (orig. Osebnosti) focuses on the life, work, and legacy of France Borko, a teacher and writer who, in the first half of the 20th century, significantly influenced the cultural life of Maribor with his dedication to writing and cultural participation. The Introduction addresses the purpose of this publication and presents the characteristics of Borko’s legacy, preserved in the Manuscript Collection of the University of Maribor Library. The central part of the publication is the presentation of Borko’s life and work, based on various documents and other sources. The biographical overview is complemented by a selection of Borko’s documentary materials, showcased in a separate chapter. Another important component is his bibliography, which systematically and comprehensively presents his life and work. As a special addition, the publication includes a list of dialect expressions from the Središče ob Dravi area, which Borko compiled on Fran Saleški Finžgar’s request.